Pharmacokinetic Variability and Clinical Use of Lacosamide in Children and Adolescents in Denmark and Norway. Issue 3 (June 2019) - Larsen Burns, Margrete; Nikanorova, Marina; Baftiu, Arton; Borg Rasmussen, Jan; Johannessen, Svein I.; Johannessen Landmark, Cecilie
Abstract : Background: The indication for the antiepileptic drug lacosamide (LCM) was recently extended to include children from the age of 4 years. Real-life data on the use and serum concentrations of LCM in children and adolescents are limited. The purpose of this study was to investigate the use of LCM in this patient group in relation to age, comedication, dose, serum concentrations and duration of treatment, and to examine pharmacokinetic variability. Methods: Children and adolescents (<18 years) who had serum concentrations of LCM measured from January 2012 to June 2018 were retrospectively identified from the therapeutic drug monitoring databases at 2 national epilepsy centers in Norway and Denmark. Clinical data were collected from request forms and medical records. Results: Data from 124 patients were included, 61 girls/63 boys. Weight was available for 76 patients. Median age was 15 years (range 2–17 years), dose of LCM 300 mg/d (76–600 mg/d), and serum concentration 18 µmol/L (5–138 µmol/L) [4.5 mg/L (1.3–34.5 mg/L)]. Pharmacokinetic variability was demonstrated as the concentration/(dose/kg) ratio ranged from 1.3 to 9.4 (µmol/L)/(mg/kg) and was affected by age. Polytherapy with 1–3 other antiepileptic drugs was noted in 107 patients (86%). Treatment was continued beyond 1 year in 71% (n = 45) of the 63 patients where such information was available, and all of these 45 patients had serum concentrations within the defined reference range. The 1-year retention rate was higher in patients not concomitantly using other sodium channel–blocking drugs (82% versus 56%). Conclusions: The study demonstrates pharmacokinetic variability in and between age groups, which indicates usefulness of therapeutic drug monitoring. More than two-thirds of patients continued treatment beyond 1 year, suggesting reasonable effectiveness.